2002
DOI: 10.1200/jco.20.5.1167
|View full text |Cite
|
Sign up to set email alerts
|

INT 0123 (Radiation Therapy Oncology Group 94-05) Phase III Trial of Combined-Modality Therapy for Esophageal Cancer: High-Dose Versus Standard-Dose Radiation Therapy

Abstract: The higher radiation dose did not increase survival or local/regional control. Although there was a higher treatment-related mortality rate in the patients assigned to the high-dose radiation arm, it did not seem to be related to the higher radiation dose. The standard radiation dose for patients treated with concurrent 5-FU and cisplatin chemotherapy is 50.4 Gy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

39
911
14
13

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,082 publications
(977 citation statements)
references
References 10 publications
39
911
14
13
Order By: Relevance
“…In the present study, the clinical complete response rate obtained with cisplatin -irinotecan and radiotherapy regimen was 58.1% (CI 95%: 43.4 -72.8%), in a range similar to that reported with a FU -cisplatin and radiotherapy regimen (Seitz et al, 1990;Poplin et al, 1996;Geh, 2002). The overall survival rate at 2 years of 27.9% (CI 95%: 13.4 -41.3%) in our study was similar to the result of standard treatment of definitive concomitant reported in the RTOG-8501 trial and the recent phase III study with chemo-radiotherapy as definitive treatment (Herskovic et al, 1992;Bedenne et al, 2002;Minsky et al, 2002;Stahl et al, 2005). All results published with cisplatin -irinotecan regimen suggest that its efficacy is similar to that of a standard regimen with FUcisplatin for response rate and overall survival (Geh, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the clinical complete response rate obtained with cisplatin -irinotecan and radiotherapy regimen was 58.1% (CI 95%: 43.4 -72.8%), in a range similar to that reported with a FU -cisplatin and radiotherapy regimen (Seitz et al, 1990;Poplin et al, 1996;Geh, 2002). The overall survival rate at 2 years of 27.9% (CI 95%: 13.4 -41.3%) in our study was similar to the result of standard treatment of definitive concomitant reported in the RTOG-8501 trial and the recent phase III study with chemo-radiotherapy as definitive treatment (Herskovic et al, 1992;Bedenne et al, 2002;Minsky et al, 2002;Stahl et al, 2005). All results published with cisplatin -irinotecan regimen suggest that its efficacy is similar to that of a standard regimen with FUcisplatin for response rate and overall survival (Geh, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, in operable patients with locally advanced oesophageal cancer, the combination of chemotherapy and concurrent radiotherapy has been demonstrated to have an outcome similar to that of surgery after preoperative therapy (Bedenne et al, 2002;Stahl et al, 2005). The standard chemotherapy regimen associates 5 Fluorouracil (FU) with cisplatin (Herskovic et al, 1992;Cooper et al, 1999) and the recommended total dose of concurrent radiation is 50 Gy (Minsky et al, 2002). A number of drugs have been tested in oesophageal cancer Geh, 2002).…”
mentioning
confidence: 99%
“…Therefore, locoregional disease was a component of treatment failure in 84% of cases, whereas metastatic disease was a component in 22%. The overall local failure rate of 42% is similar to other chemoradiation studies (Minsky et al, 2002), but possibly higher than that seen after surgery (Kelsen et al, 1998;Dresner et al, 2000).…”
Section: Discussionsupporting
confidence: 84%
“…Changing body contours and tissue densities together with the close proximity of important normal tissue structures make tumours of the oesophagus a challenging disease in which to deliver a homogenous dose of radiation, and therefore a prime tumour site in which to test innovative technologies such as intensity-modulated radiotherapy (IMRT). There is evidence for a radiation dose effect in this disease (Geh et al, 2000), though attempts to increase the dose have not yet led to an improved outcome (Minsky et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence in oesophageal cancer suggests that increasing the radiotherapy component of CRT may carry significant morbidity without benefit (Minsky et al, 2002). Consequently, in oesophageal cancer the recommended radiation dose from this series remains at 50.4 Gy.…”
Section: Discussionmentioning
confidence: 95%